An eye for an eye? Exploring the cross-linguistic phraseology of eye/øye. Issue 2 (16th October 2014) - Ebeling, Signe Oksefjell; Andersen, Gisle; Hardt, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> Previous studies have shown the productive nature of eye and how it enters into patterns of a more or less non-compositional nature (e.g. Sinclair 1991a, Więcławska 2012). This paper adds a contrastive dimension and explores the cross-linguistic phraseology of the English–Norwegian cognates eye and øye on the basis of monolingual, bilingual and multilingual corpora. Starting with a survey of uses in the bidirectional English–Norwegian Parallel Corpus+ (ENPC+), the contrastive analysis reveals that while the two languages overlap in many of their uses of eye/øye-expressions, differences also emerge, particularly with regard to the number of recurrent patterns recorded and their conditions of use. English has more recurrent patterns with eye, but Norwegian has by far the most frequent pattern, få øye på 'catch sight of' (lit.: get eye on). Following this general cross-linguistic survey, a focused contrastive case study of få øye på and its English correspondences shows how a combination of bilingual and monolingual corpora may complement each other in contrastive research. The study uncovers that English has three main correspondences – catch sight of, see and spot – of which the first is the one favoured by bilingual dictionaries. An in-depth analysis of få øye på and catch sight of and their extended context, i.e. when they are part of extended units of meaning (e.g. Sinclair 1996), suggests that although the two patterns are perfectly matched, there are substantial differences when it comes to their frequency of use. This contributes to the relatively low mutual correspondences in the bidirectional translation material at hand.